An investigation of the resurgence of yellow fever outbreak in Kwara State, Nigeria, 2018 - Awoyale, Oladayo D.; Ilesanmi, Olayinka S.; Afolabi, Aanuoluwapo A.; Fakayode, Oluwatosin E. (International Journal Of Community Medicine And Public Health, 2021)
The frequent occurrence of yellow fever (YF) outbreaks in Nigeria affirms that YF is a re-emerging public health threat. This case report therefore aimed to provide a description of a confirmed case of in Ifelodun Local Government Area of Kwara State between January and December 2018. We conducted an outbreak investigation of YF in Kwara state, Nigeria. On 18th December 2018, a 25-year-old man (Mr. A) suspected for YF was reported from Agunjin ward of Ifelodun LGA in Kwara State. Mr. A presented with a history of fever and jaundice. Laboratory investigations were conducted, and Mr. A was confirmed positive to YF Immunoglobin M from the regional World Health Organization laboratory in Dakar, Senegal, but survived the YF illness. Community survey revealed nearly 53% YF vaccination coverage using both card and history. The rapid response team in Kwara State paid courtesy visits to the palace of the Alagunjin of Agunjin who assured of the community’s cooperation. Active case search was encouraged for all healthcare workers who participated in the vaccination activity, and on-the-job trainings were conducted. To ensure 100% YF vaccine coverage in Agunjin and neighboring settlements, a mop-up vaccination program, was conducted, and all persons who received the vaccine were each issued a yellow card. To forestall a recurrence of YF outbreaks, increasing YF vaccination coverage in community settings should be promoted. Increased commitment of the government at all levels towards improving YF surveillance and providing logistics support should be prioritized.